Critical Thinking Processes of High School Students in Solving Direct and Inverse Proportions - Dyah, Nindya Waspaning; Setianingsih, Rini (Universitas Muhammadiyah Surakarta, 2019)
Critical thinking skills which are learned by students in mathematics instruction will help students solving problems they encountered in daily life. Direct and inverse proportion is a topic in mathematics which provides opportunity for students to think more critically since it is one of the most cognitively challenging topics in the school curriculum. This research is descriptive in nature aims to describe the critical thinking processes of high school students in solving direct and inverse proportions problems. It used test and interview methods to collect the data, while the subjects consisted of two grade 7 students. The research results show that students perform the following critical thinking processes: (1) conducting interpretation by categorizing what are given and asked, and clarifying meaning in detail; (2) analyzing well by examining ideas and identifying arguments as well as reasons; (3) doing inferences by querying evidence, forming hypothesis, and trying to prove the hypothesis and to draw a conclusion; (4) carrying out evaluation by assessing credibility of claims and quality of arguments before jumping to the next steps, (5) doing explanation by stating results, justifying procedures, and present arguments clearly; (6) performing self-regulation by doing monitoring and correcting what they have done.